Human immunodeficiency virus infection in a child presenting as herpes zoster ophthalmicus and non-healing keratitis - Chaudhary, M; Chaudhary, R P (Journal of Chitwan Medical College, 2017)
Herpes Zoster is produced by reactivation of latent varicella zoster from the dorsal root ganglion of sensory nerves. It is common in older individuals and rarely described in Pediatric age group. Its occurrence in younger age should be viewed with suspicion. We describe an 11-year-old Nepali child who presented with herpes zoster ophthalmicus of right half of the forehead and a perforated corneal ulcer in the right eye. On investigations he was found to have been infected with human immunodeficiency virus (HIV). Patient responded well to systemic acyclovir. Thus, herpes zoster ophthalmicus in a young child should be viewed with suspicion.